Team Productivity and Team Work: Bibliometric Analysis - Ismawati Ismawati; Madziatul Churiyah (CV. Syntax Corporation Indonesia, 2022)
It should be realized together that to develop Human Resources every organization has limitations. Therefore, it is necessary to involve other parties in the process of developing Human Resources. It is through this way that team productivity and teamwork are needed. The bibliometric literature method uses a systematic and detailed approach. This study aims to analyze the sources of literature related to keyword